Sistem Pendukung Keputusan Pemilihan Guru Terbaik Berdasarkan Penilaian Kinerja Menggunakan Metode Profile Matching - Fachry Al Hafiz; Husni Lubis; Fachrul Rozi Lubis (LKP Unity Academy, 2024)
Teachers are the initial milestone in the creation of a nation with quality young generation, both in the academic and non-academic fields. To determine or choose the best teacher, a decision support system for selecting the best teacher is made to appreciate the work performance that has been done while being a teaching staff, and is expected to increase motivation so that teachers can improve their performance. For this reason, a decision support system is needed that can analyze several teachers according to the existing teacher selection profile. The Profile Matching process is carried out to determine teacher recommendations in the Best Teacher Selection System based on 3 variables, namely intellectual aspects, work attitude aspects and general aspects. The result of the selection process is in the form of a teacher's final score as a recommendation for decision makers to choose the right teacher in the selection of the best teacher.